Prognostic Factors for Visual Outcome in Traumatic Cataract Patients - Ying Qi; Yan F. Zhang; Yu Zhu; Ming G. Wan; Shan S. Du; Zhen Z. Yue (Journal of Ophthalmology)
Purpose. To investigate the prognostic factors for visual outcome in traumatic cataract patients. Methods. The demographic features of traumatic cataract patients in Central China were studied. The factors that might influence the visual outcome were analyzed. The sensitivity and specificity of OTS (ocular trauma score) in predicting VA were calculated. Results. The study enrolled 480 cases. 65.5% of patients achieved VA at >20/60. The factors associated with the final VA were initial VA, injury type, wound location, the way of cataract removal, and IOL implantation. The sensitivities of OTS in predicting the VA at NLP (nonlight perception), LP/HM (light perception/hand motion), and ≥20/40 were 100%. The specificity of OTS to predict the final VA at 1/200-19/200 and 20/200-20/50 was 100%. Conclusion. The prognostic factors were initial VA, injury type, wound location, cataract removal procedure, and the way of IOL implantation. The OTS has good sensitivity and specificity in predicting visual outcome in traumatic cataract patients in long follow-up.